Facile Synthesis of Bis(indolyl)alkanes Catalyzed by Cu(ClO4)2.6H2O Under Solvent Free Conditions - Baruah, Mukulesh (Letters in Organic Chemistry, 2011)
Copper perchlorate hexahydrate is found to be an efficient catalyst for the electrophilic substitution of indole with carbonyl compounds to prepare bis(indolyl)methane derivatives without solvent in excellent yield at room temperature.
Keywords: alkanes